Dynamic Systems Theory and Dual Change Score Models: Seeing Teams through the Lens of Developmental Psychology - Matusik, James G.; Hollenbeck, John R.; Matta, Fadel K.; Oh, Jo K. (Academy of Management Journal, 2019)
Empirical research examining team development has long lagged behind purely conceptual work. Moreover, traditional designs and logics frequently employed in the organizational sciences generally preclude the possibility of studying the trajectories of various team properties. This is problematic as continuity, nonlinearity, and within-construct feedback are implicit in many eminent conceptualizations of teams. Hence, the present investigation integrates dynamic logic, theory, and methodology from the discipline of developmental psychology—wherein the nature of the topic has necessitated a more careful examination of change over time—into the organizational literature. As a product of this integration, we propose and test a novel theoretical perspective that provides several contributions to teams research. First, we extend theory that has thus far been primarily used to explain intraindividual development in children to detail three testable principles of dynamism in team properties. Second, and utilizing a within-construct logic, we demonstrate that teams are indeed dynamic systems, but that the extent to which any particular team property may be considered dynamic is contingent upon characteristics of the property itself. Finally, we illustrate how teams’ unique pasts may be leveraged to predict their asymmetric reactions to disruptive events in the future by employing a contemporary modeling technique.